2019
DOI: 10.2495/ei-v2-n3-283-299
|View full text |Cite
|
Sign up to set email alerts
|

Pesticide levels in streams and sediments on the islands of Oahu and Kauai, Hawaii

Abstract: A survey water quality study was conducted between 2014 and 2017 to investigate the presence and concentration of pesticides in the nearshore marine environments on the islands of Oahu and Kauai. On Kauai, a total of 32 surface water and 16 sediment samples were collected from four streams and one irrigation ditch over multiple sampling events. On Oahu, a total of 27 surface water and 16 sediment samples were collected from six streams on the leeward side of the island over multiple sampling events, typically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…a previous water quality study conducted in hawaii found widespread glyphosate contamination within surface waters and stream bed sediment on the islands of Oahu and Kauai [15]. either glyphosate or aMpa was detected in 100% of the 32 stream bed sediment samples collected from multiple streams sampled on these two islands during this study.…”
supporting
confidence: 52%
See 1 more Smart Citation
“…a previous water quality study conducted in hawaii found widespread glyphosate contamination within surface waters and stream bed sediment on the islands of Oahu and Kauai [15]. either glyphosate or aMpa was detected in 100% of the 32 stream bed sediment samples collected from multiple streams sampled on these two islands during this study.…”
supporting
confidence: 52%
“…the median half-lives determined for glyphosate and aMpa (4.7 and 6.2 days) in stream sediments in the tropical Kawa watershed are significantly lower than typical literature values for these two compounds in soils (2-215 and 60-240 days, respectively) [6,8,9]. despite the short persistence of glyphosate in the hawaiian environment, the current concentration levels are seven and ten times higher than concentration levels of persistent organic pollutants (with longer half-lives on the order of years) measured in waters and sediments in the mid-1970s on the island of Oahu [15]. this attests to the significantly higher present-day mass loading of glyphosate to the hawaiian environment than historic pesticide loading levels in urban environments.…”
mentioning
confidence: 55%